rfATOM a UHF RFID system implementation on an x86 motherboard platform - Abueg, Laurice C.; Diaz, Roma Franz Iris F.; Soriente, Cecille Anne V. (2009.)
Radio frequency identification (RFID) solutions, in general, are application-specific. In ultra-high frequency (UHF) RFID, for example, most applications are limited to inventory tracking and asset management. The project aims to develop a versatile RFID system with an internal reader-host interface, via a motherboard platform. The RFID PC system with an internal reader-host interface, via a motherboard platform. The RFID PC desktop system is designed for compactness and easy stationary deployment. UHFID tags are wirelessly identified by a SkyeTek M9 reader fixed and interfaced with an Intel desktop board through the serial port. Peripherals can be connected through the standard ports of the off-the-shelf board, and the reader uses an external antenna, allowing for greater design flexibility. The Linux-based integrated middleware and application design utilizes a web component incorporating SkyeTek Protocol v3. Three basic applications (inventory, access control and patron management) were developed along with the software development kit. Performance of the RFID system was benchmarked and optimized by monitoring read misses, redundancies, the time delay between the tag reading and the database update, accuracy of the information in relation to the actual object and the database and the appropriate application triggers upon identification of selected tags. The end product is envisioned to be compact, reconfigurable general-purpose system that can be used for personal and small business.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Radio frequency identification systems; Radio frequency -- Identification; UHF RFID system; Ultra high frequency; UHFID tags; SkyTek M9 reader